The labour market and financial consequences of relationship breakdown and re-partnering for mothers with young children - Baxter, Jennifer; Gray, M (My University, 2007)
This document features slides from a presentation on the relationships between maternal employment and partner status, with reference to the age of children. Based on data from Growing Up in Australia: the Longitudinal Study of Australian Children (LSAC), the authors examine the relationship dynamics of mothers with young children, and the impact of relationship changes on paid employment, financial well-being, and income support. The presentation features slides on the research background and methodology, the sample characteristics, maternal labour force participation, relationship changes, employment transitions, parental income, welfare income, and financial well-being and hardship. This study provides insight into the transitions and changes of the single mother population.
Keywords: Relationships; Relationships -- Dissolution; Families and relationships; Relationships; Dissolution; Families and relationships